Photovoltaic water-based flux and preparation method and application thereof

By introducing activator microcapsules wrapped with organic acids and protectants into the water-based flux, the problem of slow volatility of water-based flux in high-speed welding is solved, efficient deoxidation and protection of welding surfaces is achieved, and welding quality and joint strength are improved.

CN119216873BActive Publication Date: 2025-03-04SHENZHEN VITAL NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411719116.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing water-based flux volatilizes slowly during high-speed welding, affecting the welding quality and efficiency, and the presence of water molecules may lead to poor welding and reduce the strength and reliability of the welded joints.

Method used

Photovoltaic water-based flux is used, which consists of water, a solvent, wetting agent, polyethylene glycol, antioxidant and activator microcapsules that encapsulate organic acids and protectants. The activator microcapsules gradually decompose at high temperatures, releasing organic acids and protective agents, removing the oxide layer and forming a protective film, and improving welding quality.

Benefits of technology

It improves the strength and reliability of the welded joints, enhances welding performance, ensures that the flux can continuously provide activity during the welding process, and is suitable for the welding process with a thermal welding temperature of 150-230℃.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a photovoltaic water-based soldering flux and a preparation method and application thereof, comprising the following raw materials in parts by weight: 1-5 parts of cosolvent, 0.1-3 parts of wetting agent, 0.1-3 parts of polyethylene glycol, 1-8 parts of activator microcapsules, 0.1-1 parts of antioxidant, and 100 parts of water; wherein the activator microcapsules include capsule cores and capsule materials wrapping the capsule cores, and the capsule cores are composite activators; wherein the composite activator is a composition of an organic acid and a protective agent; the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid; the protective agent is a composition of trimethylsiloxane and a quaternary ammonium salt cationic fluorocarbon surfactant. The soldering flux of the present invention uses water as the main solvent, and the soldering flux is more suitable for the preparation of photovoltaic cell chip assemblies with a hot welding temperature of 150-230°C, and the soldering flux can continuously provide activity during welding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic soldering flux, and in particular to a photovoltaic water-based soldering flux and a preparation method and application thereof. Background Art

[0002] Water-based flux does not contain harmful substances such as halogen, rosin and resin. It is an environmentally friendly material and will not pollute the environment. They usually do not contain VOC (volatile organic compounds) and meet the requirements of air quality regulations. Existing water-based fluxes have the following major technical problems: Water is slower to volatilize than organic solvents (such as isopropyl alcohol) and requires higher temperatures to completely volatilize. During high-speed welding, this may cause the flux to fail to volatilize in time, thus affecting the welding quality and efficiency. Residual moisture may form bubbles during welding or cause poor welding, such as cold welding, etc. Due to the slow volatilization rate of water-based flux at high temperatures, the activator may not be able to fully play its role in removing oxides and promoting welding. The presence of water molecules may affect the contact and reaction between the activator and the metal surface, thereby reducing the strength and reliability of the welded joint. At the same time, water-based flux may be affected by environmental factors such as temperature and humidity during storage and use, resulting in changes in its performance. Stability issues may cause the flux to fail to achieve the expected effect during welding, thus affecting the welding quality. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a photovoltaic water-based soldering flux and a preparation method and application thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a photovoltaic water-based solder flux, comprising the following raw materials in parts by weight: 1-5 parts of a cosolvent, 0.1-3 parts of a wetting agent, 0.1-3 parts of polyethylene glycol, 1-8 parts of an activator microcapsule, and 0.1-1 part of an antioxidant, which are supplemented with water to 100 parts; wherein the activator microcapsule comprises a capsule core and a capsule material wrapping the capsule core, and the capsule core is a composite activator; the composite activator is a composition of an organic acid and a protective agent in a mass ratio of (5-8):1; wherein the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid, and methylsuccinic acid in a mass ratio of 1:1:(0.5-1.2); the protective agent is a composition of trimethylsiloxane and a quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:(1.5-2);

[0006] The preparation method of the activator microcapsule comprises the following steps:

[0007] S1, adding the organic acid and the protective agent into the alcohol solvent according to the proportion and stirring and mixing evenly, then evaporating the alcohol solvent to obtain a solid composite activator, that is, obtaining the capsule core;

[0008] S2. Add the capsule core to the chitosan solution and stir evenly, then add the gum arabic solution, adjust the pH to 4.5-5, and continue stirring at 50-55°C for 1-2h;

[0009] S3. After the stirring is completed, the temperature is lowered to below 10°C, and glutaraldehyde is added and stirred to solidify for 1-6 hours;

[0010] S4. After the curing is completed, the temperature is slowly raised to room temperature, washed with water, and dried to obtain the activator microcapsules.

[0011] The soldering flux of the present invention uses water as the main solvent, because the organic acid selected by the present invention is 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid, and the organic acid can react chemically with the oxide on the metal surface to generate soluble salts, thereby removing the oxide layer on the welding surface. The mixed use of the three acids can synergistically improve the deoxidation efficiency of the soldering flux, and oleic acid, as a long-chain fatty acid, can reduce the surface tension of the molten solder, improve the fluidity and wettability of the solder, make it easier to flow and cover the weld area, and make the organic acid more effectively remove the oxide and pollutants on the welding surface, which helps to improve the strength and reliability of the welded joint. The protective agent can form a protective film during the welding process to prevent the metal from being further oxidized at high temperatures, and this protective film helps to improve the welding quality and the corrosion resistance of the metal surface. Trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant work together to enhance the overall corrosion inhibition effect of the soldering flux. Because 3-hydroxy-2-naphthoic acid and oleic acid are both organic acids that are difficult to dissolve in water, the organic acid is wrapped in the form of microcapsules to be evenly dispersed in water.

[0012] Polyethylene glycol is completely miscible with water. Polyethylene glycol has good stability at high temperatures and will not decompose to generate harmful substances. At the same time, it has film-forming properties and can form a photovoltaic water-based flux layer on the surface of the tin-plated layer, which can prevent the volatilization of the composite activator before welding, maintain the activity of the organic acid, and provide protection at room temperature. The wetting agent can increase the affinity of the flux to the solder powder and the pad, so that the photovoltaic water-based flux can be more evenly coated on the surface of the material to be welded, which helps the expansion and spreading of the solder and improves the welding quality.

[0013] The present invention adopts complex coacervation method to prepare activator microcapsules. The main components in the activator microcapsules are organic acid and protective agent. 3-hydroxy-2-naphthoic acid, oleic acid and trimethylsiloxane are all insoluble in water. Therefore, 3-hydroxy-2-naphthoic acid, trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant are dissolved in an alcohol solvent, and the solvent is removed to obtain a solid composite activator. The solid composite activator is used as a capsule core and is wrapped in a chitosan-gelatin capsule material to prepare microcapsules. The organic acid and the protective agent are wrapped in the form of microcapsules. Because the thermal stability of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant is higher, the two can enhance the penetration of the organic acid activator in the high-temperature welding process, that is, the activity of the organic acid can be improved.

[0014] Specifically, the mechanism for preparing the activator microcapsules is as follows: the capsule core is mixed with the capsule material to form an emulsion or suspension. By adjusting the pH value of the solution, the two capsule materials undergo a cross-linking reaction due to opposite charges. Chitosan is positively charged in an acidic solution, while gum arabic is negatively charged. When the pH is adjusted to 4.5-5, the two are neutralized to form a complex due to opposite charges. Due to charge neutralization, the solubility of the capsule material is reduced, so that it condenses and precipitates in the system to form microcapsules. Then, a glutaraldehyde curing agent is added to react chemically with the capsule material, so that the capsule material molecules are cross-linked into a network structure, maintaining the shape of the microcapsules, and becoming irreversible microcapsules.

[0015] Because the capsule material of chitosan-arabic gum will gradually decompose during the high-temperature welding process, the organic acid and protective agent inside will gradually precipitate, trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant can form a protective film, covering the surface of the organic acid activator, reducing the direct effect of high temperature on the organic acid activator, helping to stabilize the structure of the organic acid activator, preventing it from decomposing at high temperature, and also playing a role of corrosion inhibition. At 100°C, water has been volatilized and will not affect the welding process. The organic acid combination selected by the present invention is 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid, both of which are high-boiling organic acids, so the flux of the present invention can maintain stability at room temperature and release activity at high temperature, so the flux of the present invention is more suitable for the welding process of hot welding temperature 150-230°C, and the flux can continue to provide activity in the welding process of preparing photovoltaic cells.

[0016] Preferably, in the preparation step S1 of the activator microcapsules, the alcohol solvent is ethanol, and the mass concentration of ethanol is 70-80%.

[0017] Preferably, in the preparation step S2 of the activator microcapsules, the mass ratio of the capsule core, chitosan and gum arabic is 2:1:(3-5), the mass concentration of the chitosan solution is 30-40wt%, and the mass concentration of the gum arabic solution is 30-40wt%.

[0018] Preferably, in step S2 of the method for preparing the activator microcapsules, an acetic acid solution with a mass concentration of 1-5% is added to adjust the pH.

[0019] In the preparation step S3 of the activator microcapsules, the added amount of glutaraldehyde is 0.01wt%-0.05wt%.

[0020] Preferably, the trimethylsiloxane is methyltris(trimethylsiloxy)silane.

[0021] Preferably, the antioxidant is hydroquinone and / or catechol.

[0022] Preferably, the co-solvent comprises at least one of isopropanol, anhydrous ethanol and methanol. More preferably, the co-solvent comprises a composition of isopropanol, anhydrous ethanol and methanol in a mass ratio of 1:(0.1-0.5):(0.1-0.5).

[0023] Preferably, the wetting agent is at least one of Span, Tween, and OP-10. The function of the wetting agent is to reduce the surface tension of water and increase the wettability of the flux; Span, Tween, and OP-10 all meet the requirements of not ionizing in water, not reacting with acids and bases, and having good solubility in water, cosolvents, and polyethylene glycol.

[0024] In a second aspect, the present invention provides a method for preparing a photovoltaic water-based flux, comprising the following steps:

[0025] Water, a cosolvent, polyethylene glycol and a wetting agent are mixed, and then an antioxidant and an activator microcapsule are added, and the photovoltaic water-based soldering flux is obtained after stirring.

[0026] In a third aspect, the present invention provides the use of photovoltaic water-based flux in the preparation of photovoltaic cell assembly.

[0027] A method for preparing a photovoltaic cell assembly comprises the following steps:

[0028] S1. Clean the surface of the solder strip, then add flux to soak it, then take out the solder strip, clean the surface of the solder strip so that there is no flux flowing on the surface, and after cleaning, place it in cotton cloth for storage;

[0029] S2, preheating the electric soldering iron to a temperature of 250-300°C, and then preheating the heating table to a temperature of 40-50°C;

[0030] S3, placing the battery cell to be welded on a preheating heating table for preheating, so that the temperature of the battery cell surface reaches 30-40°C, and then continue to heat up, so that the heating table is heated to 100-110°C;

[0031] S4, solder the solder strip to the battery cell at a soldering temperature of 150-230°C;

[0032] S5, cooling the welded cells to obtain the photovoltaic cell assembly.

[0033] Preferably, in step S4, a high-speed welding machine is used to weld the battery cell and the welding ribbon.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The soldering flux of the present invention uses water as the main solvent, and the composite activator includes an organic acid and a protective agent, wherein the organic acid is 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid, and the three synergistically improve the deoxidation efficiency of the soldering flux. However, 3-hydroxy-2-naphthoic acid and oleic acid are insoluble in water, so the organic acid and the protective agent are wrapped in the form of microcapsules, and then a wetting agent and a cosolvent are added to make the activator microcapsules uniformly dispersed in water. The protective agent is trimethylsiloxane and a quaternary ammonium salt cationic fluorocarbon surfactant, and the two synergistically enhance the overall corrosion inhibition effect of the soldering flux and play a role in preventing the organic acid from decomposing at high temperatures. The capsule material of the activator microcapsule is gradually decomposed during the high-temperature welding process, so that the organic acid and the protective agent are gradually precipitated, which plays a role in removing the oxide film, protecting the battery sheet and improving the welding performance. The organic acid combination selected by the present invention is 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid, all of which are high-boiling point organic acids. The activators can maintain stability at room temperature and release activity at high temperature. The soldering flux of the present invention is more suitable for the preparation of photovoltaic cells with a hot welding temperature of 150-230°C, and the soldering flux can continuously provide activity during the welding process at 150-230°C. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0037] The sources of the reagents used in the following examples and comparative examples are as follows:

[0038] Polyethylene glycol: polyethylene glycol 4000, manufactured by Shanghai Yuanye Biotechnology Co., Ltd., brand number S30191;

[0039] Methylsuccinic acid: manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., brand number 1033734;

[0040] 3-Hydroxy-2-naphthoic acid: manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., brand number 1046842;

[0041] Oleic acid: The manufacturer is Shanghai Yuanye Biotechnology Co., Ltd., brand S30008, purity AR;

[0042] Methyltris(trimethylsilyloxy)silane: manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand name is M833918;

[0043] Quaternary ammonium salt cationic fluorocarbon surfactant: the manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., the brand is PB20470;

[0044] Chitosan: The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., the brand is C105799; the purity is deacetylation degree ≥ 95%, and the viscosity is 100-200mpa.s;

[0045] Solder ribbon: round wire solder ribbon, the manufacturer is Jinglan Optoelectronics Technology (Jiangsu) Co., Ltd., model is φ0.30 mm.

[0046] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.

[0047] Example 1

[0048] A photovoltaic water-based soldering flux comprises the following raw materials in parts by weight: 3 parts of a solvent, 1 part of methylsuccinic acid, 1.25 parts of a wetting agent, 2 parts of polyethylene glycol, 5 parts of an activator microcapsule, and 2 parts of an antioxidant, which are supplemented with water to 100 parts; wherein the activator microcapsule comprises a capsule core and a capsule material wrapping the capsule core, the capsule core is a composite activator, the composite activator is an organic acid and a protective agent in a mass ratio of 6:1, the organic acid comprises 3-hydroxy -2-naphthoic acid, oleic acid and methylsuccinic acid, the protective agent is a composition of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:1.6, the trimethylsiloxane is methyltris(trimethylsiloxy)silane; the cosolvent includes a composition of isopropanol, anhydrous ethanol and methanol in a mass ratio of 1:0.2:0.3; the wetting agent is OP-10; the antioxidant is hydroquinone and catechol in a mass ratio of 1:1.

[0049] The preparation method of the activator microcapsule comprises the following steps:

[0050] S1, adding the organic acid and the protective agent according to the proportion to an ethanol solution with a mass concentration of 75%, stirring and mixing evenly, and then evaporating the alcohol solvent to obtain a solid composite activator, that is, obtaining the capsule core;

[0051] S2, adding the capsule core to the chitosan solution and stirring evenly, then adding the gum arabic solution, adding acetic acid solution with a mass concentration of 3% to adjust the pH to 4.5, and continuing stirring at 55°C for 1.5 hours, wherein the mass ratio of the capsule core, chitosan and gum arabic is 2:1:4; the mass concentration of the chitosan solution is 35wt%, and the mass concentration of the gum arabic solution is 35wt%;

[0052] S3, after the stirring is completed, the temperature is lowered to 8°C, glutaraldehyde is added, stirred and solidified for 3 hours, wherein the amount of glutaraldehyde added is 0.02wt%;

[0053] S4. After the curing is completed, the temperature is slowly raised to room temperature, washed with water, and dried to obtain the activator microcapsules.

[0054] The preparation method of photovoltaic water-based soldering flux comprises the following steps:

[0055] Water, a cosolvent, polyethylene glycol and a wetting agent are mixed, and then an antioxidant and an activator microcapsule are added, and the photovoltaic water-based soldering flux is obtained after stirring.

[0056] Example 2

[0057] A photovoltaic water-based soldering flux comprises the following raw materials in parts by weight: 1 part of cosolvent, 0.5 part of methylsuccinic acid, 0.1 part of wetting agent, 0.1 part of polyethylene glycol, 1 part of activator microcapsule, 0.1 part of antioxidant, and the weight is supplemented by water to 100 parts; wherein the activator microcapsule comprises a capsule core and a capsule material wrapping the capsule core, and the capsule core is a composite activator; wherein the composite activator is an organic acid and a protective agent in a ratio of 5:1; the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:0.5; the protective agent is a composition of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:1.5; the trimethylsiloxane is methyl tris(trimethylsiloxy)silane. The cosolvent comprises a composition of isopropanol, anhydrous ethanol and methanol in a mass ratio of 1:0.1:0.1; the wetting agent is Span 80. The antioxidant is hydroquinone.

[0058] The preparation method of the activator microcapsule comprises the following steps:

[0059] S1, adding the organic acid and the protective agent according to the proportion to an ethanol solution with a mass concentration of 70%, stirring and mixing evenly, and then evaporating the alcohol solvent to obtain a solid composite activator, that is, obtaining the capsule core;

[0060] S2, adding the capsule core to the chitosan solution and stirring evenly, then adding the gum arabic solution, adding acetic acid solution with a mass concentration of 1% to adjust the pH to 4.5, and continuing stirring at 50°C for 2 hours, wherein the mass ratio of the capsule core, chitosan and gum arabic is 2:1:3; the mass concentration of the chitosan solution is 30wt%, and the mass concentration of the gum arabic solution is 30wt%;

[0061] S3, after the stirring is completed, the temperature is lowered to 5°C, glutaraldehyde is added, stirred and solidified for 1 hour, wherein the amount of glutaraldehyde added is 0.01wt%;

[0062] S4. After the curing is completed, the temperature is slowly raised to room temperature, washed with water, and dried to obtain the activator microcapsules.

[0063] The preparation method of photovoltaic water-based soldering flux comprises the following steps:

[0064] Water, a cosolvent, polyethylene glycol and a wetting agent are mixed, and then an antioxidant and an activator microcapsule are added, and the photovoltaic water-based soldering flux is obtained after stirring.

[0065] Example 3

[0066] A photovoltaic water-based soldering flux comprises the following raw materials in parts by weight: 5 parts of cosolvent, 2 parts of methylsuccinic acid, 3 parts of wetting agent, 3 parts of polyethylene glycol, 8 parts of activator microcapsules, and 1 part of antioxidant, which are supplemented with 100 parts of water; wherein the activator microcapsules comprise a capsule core and a capsule material wrapping the capsule core, and the capsule core is a composite activator; wherein the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 8:1; the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:1.2; the protective agent is a composition of trimethylsiloxane and a quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:2; the trimethylsiloxane is methyltris(trimethylsiloxy)silane. The cosolvent comprises a composition of isopropanol, anhydrous ethanol and methanol in a mass ratio of 1:0.5:0.5. The wetting agent is Tween. The antioxidant is catechol.

[0067] The preparation method of the activator microcapsule comprises the following steps:

[0068] S1, adding the organic acid and the protective agent according to the proportion to 80% ethanol by mass concentration and stirring and mixing evenly, then evaporating the alcohol solvent to obtain a solid composite activator, that is, obtaining the capsule core;

[0069] S2. Add the capsule core to the chitosan solution and stir evenly, then add the gum arabic solution, add acetic acid solution with a mass concentration of 5% to adjust the pH to 5, and continue stirring at 55°C for 1 hour; the mass ratio of the capsule core, chitosan and gum arabic is 2:1:5. The mass concentration of the chitosan solution is 40wt%, and the mass concentration of the gum arabic solution is 40wt%.

[0070] S3. After the stirring is completed, the temperature is lowered to 10° C., glutaraldehyde is added, and the stirring is performed for curing for 6 hours; the amount of glutaraldehyde added is 0.05 wt %.

[0071] S4. After the curing is completed, the temperature is slowly raised to room temperature, washed with water, and dried to obtain the activator microcapsules.

[0072] The preparation method of photovoltaic water-based soldering flux comprises the following steps:

[0073] Water, a cosolvent, polyethylene glycol and a wetting agent are mixed, and then an antioxidant and an activator microcapsule are added, and the photovoltaic water-based soldering flux is obtained after stirring.

[0074] Example 4

[0075] The difference between Example 4 and Example 1 is that the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 5:1.

[0076] Example 5

[0077] The difference between Example 5 and Example 1 is that the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 7:1.

[0078] Example 6

[0079] The difference between Example 6 and Example 1 is that the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 8:1.

[0080] Example 7

[0081] The difference between Example 7 and Example 1 is that the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:0.5.

[0082] Example 8

[0083] The difference between Example 8 and Example 1 is that the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:0.8.

[0084] Example 9

[0085] The difference between Example 9 and Example 1 is that the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:1.2.

[0086] Example 10

[0087] The difference between Example 10 and Example 1 is that the protective agent is a composition of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:1.5.

[0088] Embodiment 11

[0089] The difference between Example 11 and Example 1 is that the protective agent is a composition of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:1.8.

[0090] Example 12

[0091] The difference between Example 12 and Example 1 is that the protective agent is a composition of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:2.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that the organic acid is not added in the form of microcapsules, but is directly added to the system after the stirring in step S3 is completed.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that no organic acid is added.

[0096] Comparative Example 3

[0097] The difference between Comparative Example 3 and Example 1 is that 3-hydroxy-2-naphthoic acid is not added.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 1 is that oleic acid is not added.

[0100] Comparative Example 5

[0101] The difference between Comparative Example 5 and Example 1 is that methylsuccinic acid is not added.

[0102] Comparative Example 6

[0103] The difference between Comparative Example 6 and Example 1 is that the protective agent is not added in the form of microcapsules, but is directly added to the system after the stirring in step S3 is completed.

[0104] Comparative Example 7

[0105] The difference between Comparative Example 7 and Example 1 is that no protective agent is added.

[0106] Comparative Example 8

[0107] The difference between Comparative Example 8 and Example 1 is that trimethylsiloxane is not added.

[0108] Comparative Example 9

[0109] The difference between Comparative Example 9 and Example 1 is that no quaternary ammonium salt cationic fluorocarbon surfactant is added.

[0110] Comparative Example 10

[0111] The difference between Comparative Example 10 and Example 1 is that the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 4:1.

[0112] Comparative Example 11

[0113] The difference between Comparative Example 11 and Example 1 is that the composite activator is a composition of an organic acid and a protective agent in a mass ratio of 9:1.

[0114] Comparative Example 12

[0115] The difference between Comparative Example 12 and Example 1 is that the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:0.4.

[0116] Comparative Example 13

[0117] The difference between Comparative Example 13 and Example 1 is that the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:1.3.

[0118] Performance Testing

[0119] Photovoltaic cell assemblies were prepared using the soldering fluxes prepared in Examples 1-12 and Comparative Examples 1-13.

[0120] A method for preparing a photovoltaic cell assembly comprises the following steps:

[0121] S1. Clean the surface of the solder strip, then add flux and soak it for 7 minutes, then take out the solder strip and remove excess flux with an air knife. When removing, control the amount of liquid taken out to 5%. Clean the surface of the solder strip so that there is no flux flowing on its surface; the thickness of the flux retention layer is 4-5μm.

[0122] S2, preheating the electric soldering iron to a temperature of 260° C., and then preheating the heating table to a temperature of 45° C.;

[0123] S3, placing the battery cell to be welded on a preheating heating table for preheating, so that the temperature of the battery cell surface reaches 35°C, and then continue to heat up, so that the heating table is heated to 100°C;

[0124] S4, welding the welding strip to the battery cell, the welding temperature is 200°C, and the welding time is 2s;

[0125] S5, cooling the welded cells to obtain the photovoltaic cell assembly.

[0126] The flux container used in the present invention is sealed. Before the test, the amount of flux in the container is weighed and recorded as x kg. After producing n kg of battery cells, the weight of the flux is weighed again and is y kg. Then, the amount of flux carried out is equal to (xy) kg. The calculation formula for the amount of flux carried out A for producing 1 kg of battery cells is shown in the following formula (1):

[0127] A(%)=(xy)*100% / n (1);

[0128] The calculation formula of the activator retention amount is shown in the following formula (2):

[0129] B(%)=A*C (2);

[0130] Where: C is the specific gravity of the activator in the water-based flux solution, unit: %; the specific gravity of the activator in the water-based flux solution refers to the mass ratio of methylsuccinic acid and activator microcapsules in the water-based pre-coating flux. The data of the activator retention in each group are shown in Table 1.

[0131] The photovoltaic cell modules prepared in Examples 1-12 and Comparative Examples 1-13 were used to measure the average tensile force between the cell and the welding strip after welding and the cold welding rate of the cell. Then, the cell and the welding strip were welded at 150°C and 230°C respectively using the flux prepared in Example 1, and then the average tensile force between the cell and the welding strip and the cold welding rate of the cell were measured. The test data are shown in Table 1. Cold welding refers to the failure of the welding strip on the cell to be welded to the main grid line of the cell, resulting in a small cell unit unable to contact and conduct electricity, forming a short circuit phenomenon.

[0132] Table 1 Test data of each group

[0133] Group / Performance Flux Retention % Welding tension (N) Cold soldering rate% Example 1 0.69 3.26 0.94 Example 1 (150°C) 0.92 2.74 1.40 Example 1 (230°C) 0.65 2.96 1.28 Example 2 0.92 2.01 2.14 Example 3 0.66 2.37 1.36 Example 4 0.89 2.04 1.94 Example 5 0.74 2.25 1.46 Example 6 0.81 2.18 1.61 Example 7 0.62 2.39 1.32 Example 8 0.57 2.54 1.30 Example 9 0.73 2.76 1.05 Example 10 0.57 2.98 0.98 Embodiment 11 0.61 2.72 1.18 Example 12 0.65 2.26 1.27 Comparative Example 1 0.97 1.36 16.22 Comparative Example 2 0.24 0.55 24.38 Comparative Example 3 0.38 1.38 7.23 Comparative Example 4 0.36 1.42 8.15 Comparative Example 5 0.38 1.33 8.83 Comparative Example 6 0.71 2.09 6.57 Comparative Example 7 0.26 0.47 7.60 Comparative Example 8 0.45 1.72 4.16 Comparative Example 9 0.51 1.84 4.71 Comparative Example 10 1.85 2.35 5.32 Comparative Example 11 0.72 2.11 5.18 Comparative Example 12 0.68 2.16 3.41 Comparative Example 13 0.71 2.21 3.28

[0134] Examples 1, 4-6 and comparative examples 10-11 explore the effect of the mass ratio range of the organic acid and the protective agent in the composite activator on the performance. Combined with the data, it can be seen that the mass ratio of the organic acid and the protective agent is 1:5-7, and the most preferred is 1:6. If the mass ratio of the organic acid and the protective agent is lower than 5:1, it means that the amount of the protective agent added is too much, resulting in a residual amount exceeding 1%, there will be obvious white residues, and after complete solidification, a brittle, easy-to-fall-off substance will be formed. If the mass ratio of the organic acid and the protective agent is higher than 8:1, the amount of organic acid added is too high, resulting in enhanced corrosion of the flux, damage to the welding material, further affecting the strength and toughness of the welded joint, and reducing the welding tension. At the same time, it will interfere with the wettability during the welding process, making it impossible for the solder to fully penetrate the surface of the welding object, resulting in an increase in the false soldering rate. Therefore, the present invention selects a composite activator as a composition of an organic acid and a protective agent with a mass ratio of (5-8):1, more preferably (5-7):1.

[0135] Examples 1, 7-9 and comparative examples 12-13 explored the influence of the mass ratio of the three components in the organic acid. Combined with the data, it can be seen that within the optional range, the preferred mass ratio of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in the organic acid is 1:1:(1.2-1.6).

[0136] Examples 1, 10-12 explore the effect of the mass ratio of the two components of the protective agent on the performance of the flux. Combined with the data, it can be seen that if the mass ratio of the composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in the organic acid is not within the range of 1:1:(0.5-1.2), its performance is significantly reduced. Within the optional range, the preferred mass ratio of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant in the protective agent is 1:(1.5-1.6).

[0137] In Comparative Example 1, the composite activator is added directly, not in the form of microcapsules. Because 3-hydroxy-2-naphthoic acid and oleic acid are both water-insoluble acids, the soldering flux cannot form a uniform coating on the surface of the soldering strip, which interferes with the wettability during the welding process, making it impossible for the solder to fully penetrate the surface of the welding object, and the direct addition of organic acid will increase the corrosiveness of the soldering strip and the surface of the battery cell, thereby significantly reducing the welding tension and increasing the false welding rate. Therefore, the present invention wraps the organic acid in the form of microcapsules, so that it can be evenly dispersed in the soldering flux, which is convenient for forming a uniform coating, and the protective agent and the organic acid are placed in the capsule core together, and when precipitated, the protective agent can play a corrosion inhibition role.

[0138] The performance of Comparative Example 1 is significantly reduced compared with Example 1 and Comparative Examples 3-4, indicating that 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid have a synergistic effect to improve the deoxidation efficiency of the flux. At the same time, oleic acid, as a long-chain fatty acid, can reduce the surface tension of the molten solder, improve the fluidity and wettability of the solder, make it easier to flow and cover the weld area, and enable the organic acid to more effectively remove oxides and contaminants on the welding surface, which helps to improve the strength and reliability of the battery cell welding.

[0139] In comparative example 6, the protective agent is not added in the form of microcapsules, but is directly added and mixed with the other raw materials. Because the protective agent also has film-forming properties, making the protective agent contact the welding strip before the organic acid is added will affect the organic acid's removal of oxides and pollutants on the welding surface, thereby reducing the performance of the soldering flux. Therefore, the present invention adds the organic acid and the protective agent in the form of microcapsules, and after the capsule material of the microcapsule is decomposed by high temperature, the effective components of the capsule core are precipitated, which can ensure the active effect of the organic acid while enabling the protective agent to play a role in corrosion inhibition.

[0140] The performance of Comparative Example 7 is significantly reduced compared with Comparative Examples 8-9 and Example 1, indicating that the protective agent of the combination of trimethylsiloxane and quaternary ammonium salt cationic fluorocarbon surfactant has a synergistic effect, which can reduce the direct effect of high temperature on the organic acid activator, help stabilize the structure of the organic acid activator, prevent it from decomposing at high temperature, and also play a role in corrosion inhibition.

[0141] The present invention also explores the soldering effect of the soldering flux of Example 1 at 150°C, 200°C and 230°C respectively. The soldering flux performance is 200°C>230°C>150°C from high to low. If the temperature is 150°C, the organic acids used in the present invention are all high boiling points, and the soldering temperature is low, so the activity of the organic acids cannot be stimulated. Therefore, the soldering flux of the present invention is more preferably used at a temperature of 200-230°C.

[0142] In summary, the soldering flux of the present invention is more suitable for preparing photovoltaic cell modules with a hot welding temperature of 150-230° C. The soldering flux can continuously provide activity during the soldering process at 150-230° C. The soldering flux ensures that the activator can maintain stability at room temperature and release activity at high temperature.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A photovoltaic water-based flux, characterized in that: The invention comprises the following raw materials in parts by weight: 1-5 parts of cosolvent, 0.1-3 parts of wetting agent, 0.1-3 parts of polyethylene glycol, 1-8 parts of activator microcapsules, and 0.1-1 parts of antioxidant, which are supplemented with water to 100 parts; wherein the activator microcapsules comprise a capsule core and a capsule material wrapping the capsule core, the capsule core is a composite activator, the composite activator is a composition of an organic acid and a protective agent in a mass ratio of (5-8):1, the organic acid is a composition of 3-hydroxy-2-naphthoic acid, oleic acid and methylsuccinic acid in a mass ratio of 1:1:(0.5-1.2), the protective agent is a composition of trimethylsiloxane and a quaternary ammonium salt cationic fluorocarbon surfactant in a mass ratio of 1:(1.5-2); the capsule material is a chitosan-gum arabic polymer; The preparation method of the activator microcapsule comprises the following steps: S1, adding the organic acid and the protective agent into the alcohol solvent according to the proportion and stirring and mixing evenly, then evaporating the alcohol solvent to obtain a solid composite activator, that is, obtaining the capsule core; S2. Add the capsule core to the chitosan solution and stir evenly, then add the gum arabic solution, adjust the pH to 4.5-5, and continue stirring at 50-55°C for 1-2h; S3. After the stirring is completed, the temperature is lowered to below 10°C, and glutaraldehyde is added and stirred to solidify for 1-6 hours; S4. After the curing is completed, the temperature is slowly raised to room temperature, washed with water, and dried to obtain the activator microcapsules.

2. The photovoltaic water-based soldering flux according to claim 1, characterized in that: In the preparation step S2 of the activator microcapsules, the mass ratio of the capsule core, chitosan and gum arabic is 2:1:(3-5).

3. The photovoltaic water-based soldering flux according to claim 1, characterized in that: In the preparation step S3 of the activator microcapsules, the added amount of glutaraldehyde is 0.01wt%-0.05wt%.

4. The photovoltaic water-based soldering flux according to claim 1, characterized in that: Each raw material in the photovoltaic water-based soldering flux satisfies at least one of the conditions (I) to (IV): (I) the trimethylsiloxane is methyltris(trimethylsiloxy)silane; (II) the antioxidant is hydroquinone and / or catechol; (III) the co-solvent comprises at least one of isopropanol, anhydrous ethanol and methanol; (IV) The wetting agent is at least one of Span, Tween, and OP-10.

5. The photovoltaic water-based soldering flux according to claim 1 or 4, characterized in that: The co-solvent is a composition of isopropanol, anhydrous ethanol and methanol in a mass ratio of 1:(0.1-0.5):(0.1-0.5).

6. The method for preparing the photovoltaic water-based soldering flux according to any one of claims 1 to 5, characterized in that: The following steps are involved: Water, a cosolvent, polyethylene glycol and a wetting agent are mixed, and then an antioxidant and an activator microcapsule are added, and the photovoltaic water-based soldering flux is obtained after stirring.

7. Use of the photovoltaic water-based flux according to any one of claims 1 to 5 in the preparation of photovoltaic cell modules.

8. The use according to claim 7, characterized in that The method for preparing the photovoltaic cell assembly comprises the following steps: S1. Clean the surface of the solder strip, then add flux and soak it for 6-8 minutes, then take out the solder strip and clean the surface of the solder strip so that there is no flux flowing on the surface; S2, preheating the electric soldering iron to a temperature of 250-300°C, and then preheating the heating table to a temperature of 40-50°C; S3, placing the battery cell to be welded on a preheating heating table for preheating, so that the temperature of the battery cell surface reaches 30°C-40°C, and then continue to heat up, so that the heating table is heated to 100-110°C; S4, solder the solder strip to the battery cell at a soldering temperature of 150-230°C; S5, cooling the welded cells to obtain the photovoltaic cell assembly.

9. The use according to claim 8, characterized in that In step S4, a high-speed welding machine is used to weld the battery cell and the welding ribbon.

Citation Information

Patent Citations

  • High-activity scaling powder for photovoltaic solder strip

    CN105269181A

  • Flux for high-tensile strength photovoltaic module

    CN105855746A

Cited By

  • Water-based soldering flux for photovoltaic N-type battery 0BB assembly and preparation method of water-based soldering flux

    CN120438896A